Shopping Cart Analysis to Support Business Management with the Apriori Algorithm - Nurul Aini; Eka Praja Wiyata man; Muhammad Afdhal (Universitas Putra Indonesia YPTK Padang, 2024)
The increasingly advanced development of the business world has led to increasingly fierce competition. One way to maintain the company's survival is to maintain good relationships with customers. Each market has its own way of increasing sales. Serambi Mart is one of the minimarkets operating in Batusangkar City. This minimarket is relatively new because it has been operating since 2020. Even though it is new, this minimarket is quite busy with consumers visiting for shopping, this is due to Serambi Mart management choosing the right location. Based on observations made, product layout arrangements are still based on subjective management, so there are several products that are not suitable to be compared. The layout seems messy, causing difficulties for consumers in shopping. By utilizing sales transaction data at Serambi Mart. This research uses the Apriori algorithm. The Apriori algorithm is an association rule and looks for relationship patterns between one or more items in data, using Association Rules with Minimum Support of 30% and Minimum Confidence of 50%. Therefore, an application is needed that can help Serambi Mart to get information. One way to get this information is to utilize data mining techniques. By using the Apriori Algorithm method for arranging the product layout at Serambi Mart, it is hoped that it can provide convenience to consumers who shop